Exploring the Effectiveness of GOLTEEN Website-Based Application in Enhancing Adolescent Sexual Behavior Knowledge - Sari, Gita Nirmala; Aticeh, Aticeh; Baharudin, Tengku Farah Zahrani; Eprila, Eprila (Poltekkes Kemenkes Palu, 2024)
Introduction: A survey conducted by the Ministry revealed that approximately 62.7% of Indonesian adolescents have engaged in sexual activity before marriage. Objective: This study aims to assess the effectiveness of the GOLTEEN application in enhancing adolescents' knowledge of sexual behavior. Methods: A pre-experimental design was utilized, with 37 students from a senior high school in Jakarta participating. Participants completed pre-test and post-test surveys to evaluate their knowledge levels before and after exposure to the GOLTEEN application. Statistical analyses, including the Wilcoxon test, were employed to determine the significance of any observed changes in knowledge. Results: The study found a statistically significant improvement in knowledge scores after the intervention (p<0.001). Participants demonstrated a substantial increase in their understanding of sexual behavior following their engagement with the GOLTEEN application. Notably, all respondents showed improvement in their knowledge levels, with no participants exhibiting a decrease in their scores. Conclusion: The findings suggest that the GOLTEEN application serves as an effective instrument for promoting sexual health education among adolescents. By harnessing web-based applications such as GOLTEEN, educators and health practitioners can disseminate critical information and elevate awareness regarding sexual behavior among youth more effectively. This underscores the significance of integrating technology-driven methodologies within public health interventions and educational programs designed to address pivotal issues related to adolescent sexual health.